Hubungan Pengetahuan dengan Perilaku Swamedikasi Obat Antinyeri di Apotek X di Kota Denpasar: berdasarkan Theory of Planned Behavior (TPB) - Ni Made Maharianingsih; Ni Luh Mia Jasmiantini; Gde Palguna Reganata; Ni Putu Aryati Suryaningsih; I Gusti Ayu Rai Widowati (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Self-medication behavior is usually carried out to deal with complaints and minor ailments that many people experience, such as fever, pain, dizziness, cough, influenza, stomach ulcers, intestinal worms, diarrhea, skin diseases and others. The formation of behavior is influenced by knowledge. Behavior can be researched using the Theory of Planned Behavior (TPB) method. The purpose of this study was to determine the relationship between the level of knowledge and the behavior of self-medication of analgesic medication at Pharmacy X in Denpasar City. This study uses a survey method with a cross sectional approach. The sampling technique in this study used the convenience sampling method with the number of respondents in this study as many as 276 people with inclusion criteria, namely respondents who used pain medication without a doctor's prescription, aged 15-65 years, could read and write, were willing to fill out a questionnaire while the exclusion criteria were respondents with mental and physical disabilities.The instrument used in this study was a self-medication knowledge and behavior questionnaire that had been tested for validity and reliability with valid and reliable results. The data obtained were analyzed by the Somers'd correlation method because both use an ordinal scale. The results showed that the level of knowledge of the respondents was high 37,3%, moderate 33,7%, and low 29%. Respondents' behavior was divided into 3 categories of TPB, attitudes towards behavior with moderate results (47,1%), subjective norms with high results (43,1%) and behavioral control with high results (48,9%). The results of the correlation test show a significance value (p-value) of 0.000 (p<0.05), which means that there is a significant relationship. The conclusion of this study is that there is a relationship between the level of knowledge and the behavior of self-medication of analgesic medication at Pharmacy X in Denpasar City.